Guidance of zoospores by potassium gradient sensing mediates aggregation. Issue 157 (7th August 2019) - Galiana, Eric; Cohen, Celine; Thomen, Philippe; Etienne, Catherine; Noblin, Xavier
Abstract : The biflagellate zoospores of some phytopathogenic Phytophthora species spontaneously aggregate within minutes in suspension. We show here that Phytophthora parasitica zoospores can form aggregates in response to a K + gradient with a particular geometric arrangement. Using time-lapse live imaging in macro- and microfluidic devices, we defined (i) spatio-temporal and concentration-scale changes in the gradient, correlated with (ii) the cell distribution and (iii) the metrics of zoospore motion (velocity, trajectory). In droplets, we found that K + -induced aggregates resulted from a single biphasic temporal sequence involving negative chemotaxis followed by bioconvection over a K + gradient concentration scale [0–17 mM]. Each K + -sensing cell moved into a region in which potassium concentration is below the threshold range of 1–4 mM, resulting in swarming. Once a critical population density had been achieved, the zoospores formed a plume that migrated downward, with fluid advection in its wake and aggregate formation on the support surface. In the microfluidic device, the density of zoospores escaping potassium was similar to that achieved in droplets. We discuss possible sources of K + gradients in the natural environment (zoospore population, microbiota, plant roots, soil particles), and implications for the events preceding inoculum formation on host plants.